Peptides as a platform for targeted therapeutics for cancer: peptide–drug conjugates (PDCs). (21st December 2020) - Cooper, Bethany M.; Iegre, Jessica; O' Donovan, Daniel H.; Ölwegård Halvarsson, Maria; Spring, David R.
Abstract : A tutorial review showcasing how peptide–drug conjugates can offer the versatility needed for a successful drug discovery approach, their problems and future opportunities. Abstract : Peptides can offer the versatility needed for a successful oncology drug discovery approach. Peptide–drug conjugates (PDCs) are an emerging targeted therapeutic that present increased tumour penetration and selectivity. Despite these advantages, there are still limitations for the use of peptides as therapeutics exemplified through their slow progression to get into the clinic and limited oral bioavailability. New approaches to address these problems have been studied and successfully implemented to enhance the stability of peptides and their constructs. There is great promise for the future of PDCs with two molecules already on the market and many variations currently undergoing clinical trials, such as bicycle-toxin conjugates and peptide–dendrimer conjugates. This review summarises the entire process needed for the design and successful development of an oncology PDC including chemical and nanomaterial strategies to enhance peptide stability within circulation, the function of each component of a PDC construct, and current examples in clinical trials.